Cross-Country Report on Inflation : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper examines the causes and drivers of low inflation in European inflation targeting countries outside the euro area, focusing on the Czech Republic, Poland, Sweden, and Switzerland. It estimates the effects on inflation from the output gap and external factors, including oil price changes, nominal effective exchange rate (NEER) fluctuations, and euro area inflation spillovers. It is observed that external factors have been significant drivers of low inflation recently, though their contributions to inflation and the channels through which they operate vary across countries. Policy responses and options are also discussed, taking into account country-specific circumstances.